Kumbang Pupus Pisang: Hama Baru? - Dwinardi Apriyanto; Ishak Manti (Jurnal Perlindungan Tanaman Indonesia, 2006)
Many insects have been reported as pests of banana, among which the corm borer (Cosmopolites sordidus Germar) and pseudo-stem borer (Odoiphorus longicollis [Oliver]) are considered as the most important species. We found a beetle species during 2003 pest survey of banana in Rejang Lebong, Bengkulu, that had not been reported before in any publication. The adult feeds on and damages whorl of banana, and therefore we named it as "banana whorl beetle". The adult feeds on whorl causing irreguler elongated holes, forming a pattern of more or less parallel with leaf midrib when the leaf has fully opened. The holes often fuse and form larger ones. The larvae bores and tunnels into leaf midrib and pseudostem, very often from the base of leaf midribs, and develop to pupae inside the tunnel. Feeding activity of larvae and adult on banana cause serious growth retardation and failure to flowering. The beetle is sluggish, stays inside whorl or at the base of leaf midribs. It is bright/light brown in color, rather flattened, elongated, 17-19 mm length and 4.5-5.5 mm wide. The antennae are filiform, half of the body in length, consist of 11 segments. The elytra cover the whole abdomen, with parallel lines along them. Tarsi consist of four segment. The larvae have a bristle like structure along side the lateral and anal forceps at the tip of abdomen. Thoracic legs are absent. This beetle belongs to the family Chrysomelidae and subfamily Hispinae. The distribution of this insect is restricted to the area >400 m asl. and serious damages often occur above >700 m asl.